The Concept of Property Ownership in the Qur’an: A Thematic Study of Individual Rights and Social Responsibility - Salam, Selmiana; Wulandari, Devy; Sari, Dian; Ilham, Rizky Amaliyah Ramdhani; Masse, Rahman Ambo (Pustaka Peradaban, 2025)
The concept of property ownership in the Qur'an has two main dimensions: individual rights and social responsibility. The Qur'an emphasizes that wealth is a trust from Allah that can be owned personally, but its use must be in accordance with the principles of justice and the public good. This research uses a thematic interpretation method (tafsir maudhu'i), by collecting and analyzing Qur'anic verses related to property ownership, as well as considering historical context (asbāb al-nuzūl) and linguistic aspects. The results of the study show that Islam not only recognizes the individual's right to property, but also requires social responsibility, such as zakat, infaq, and the prohibition of hoarding wealth. Thus, the concept of ownership in Islam is not absolute, but is tied to ethical values and social justice. Property ownership is seen as a means to realize common prosperity and overcome social inequality. The emphasis on a balance between private property and social contribution reflects the main purpose of Islamic law in creating justice and benefit. Therefore, the concept of wealth in the Qur'an is an important foundation for the development of an economic system that is oriented towards value and balance.